Measuring democracy - Tommy Krieger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
This short article contributes to the Elgar Encyclopedia of Public Choice by summarizing the literature on the measurement of democracy. I proceed in two step. In the first part, I describe the classical approach for producing a measure of democracy and sketch an alternative approach. The second part provides an overview about existing democracy index.
Keywords: C43; O43; P00; 330; Democracy; index numbers; measurement of democracy; political institutions; regime classification